Chapter 17. A critical appraisal of the Sovereign Green Islamic Bond: case study in Indonesia - Laila, Nisful (Islamic finance in the digital age, 2024)
The goal of this chapter is to critically assess the first ever Green Islamic Bond issued by the Indonesian government. It caters for the green environmental related issue including climate change. In order to provide the analysis of Sovereign Green Islamic Bond from various aspects. This study adopts qualitative method combining literature studies and in-depth interview with the relevant person from Ministry of Finance as the Islamic Bond issuer. The finding suggests that the Indonesian Green Sovereign Islamic Bond provides great benefits for investors, such as competitive rates, risk free investment, and also can be bought by individual investors in the domestic market (for retail series) and in the global market (for global Islamic Bond series). This study shall be the main reference for the other governments to adopt the similar instrument. Using green financing framework, this Islamic bond may lead to achieve Sustainable Development Goals (SDGs).